Training of Trainer (TOT) / Nadiah Mohamed, Siti Noor Dina Ahmad and Mahfuzah Mahayadin - Mohamed, Nadiah; Ahmad, Siti Noor Dina; Mahayadin, Mahfuzah (Universiti Teknologi MARA, Negeri Sembilan, 2023)
On 15th March 2023, the College of Computing, Informatics, and Media Studies UiTM Negeri Sembilan Kampus Kuala Pilah hosted Training of Trainer (TOT) event. 15 lecturers participated in this course, which was handled by 4 skilled trainers. The participants are exposed to the correct technique to monitor students and the way to choose an appropriate title for the final year project group. It is hoped that this program will increase the spirit and motivation among lecturers to be active in research, writing, and presenting research results at various levels in addition to being able to empower knowledge among lecturers in faculty. Positive feedback was also provided by the lecturers who participated throughout the program. Figures 1 and 2 show presenters and lecturers who attend the program.